Kinematics Analysis of Sewing Robot based on Double Quaternion - Xin Yan; Liping Ma; Xiaohua Wang; Nan Wu (Jixie chuandong)
Aiming at the problems of low calculation efficiency and singularity in the traditional D-H method and spinor method for robot kinematics analysis， the kinematics parameters of sewing robot are solved by using double quaternion. The kinematics equations of the sewing robot in double quaternion form are established， and the Dixon resultant is constructed using the elimination method to solve the kinematic parameters. The kinematics simulation is performed in a limited working range. The simulation results show that the method has high computing efficiency， which is about 10% faster than the D-H method， and can provide a theoretical basis for the motion control of the robot textile sewing process.